Methods of controlling the course for an self-driving grader - R. Yu. Sukharev (Вестник СибАДИ, 2022)
Introduction. The widespread introduction of unmanned technologies quickly captures various industries and economies. Unmanned taxis are already moving through the streets of cities, including in our country. The introduction of unmanned technologies in the construction industry, namely in construction machines is a promising direction that will develop quite rapidly in the next few years. The construction machine closest in terms of control algorithm to an unmanned vehicle is an auto grader. One of the first stages of creating an unmanned grader is the construction of its trajectory. This paper presents methods for controlling the course of an unmanned vehicle, which can be adapted to control the grader.Materials and methods. Theoretical studies were carried out on a mathematical model of the working process of the grader, developed using the methodology of system analysis and presented by differential equations of the second order.Results. An efficiency criterion is proposed by which management methods can be compared. To evaluate the effectiveness of the presented methods, theoretical studies of the mathematical model of the working process of the grader were carried out according to the proposed efficiency criterion. The effectiveness of the copier control method for various values of the base length, base coefficient and grader speed has been confirmed. Conclusion. The proposed control methods can be used to create promising autonomous traffic control systems for graders and other road construction vehicles.